2018
DOI: 10.1101/487314
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trogocytosis by Entamoeba histolytica mediates acquisition and display of human cell membrane proteins and evasion of lysis by human serum

Abstract: Entamoeba histolytica is the protozoan parasite responsible for amoebiasis. We previously showed that E. histolytica kills human cells through a mechanism that we termed trogocytosis (trogo-: nibble), due to its resemblance to trogocytosis in other organisms. In parasites, trogocytosis is used to kill host cells. In multicellular organisms, trogocytosis is used for cell-cell interactions in the immune system, in the central nervous system, and during development. Thus, nibbling is an emerging theme in cell-cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…All of these processes require coordinated regulation of signal transduction, cytoskeletal reorganization, and vesicular trafficking (Aguilar‐Rojas, Olivo‐Marin, & Guillen, 2016; Babuta, Bhattacharya, & Bhattacharya, 2020; Nozaki & Nakada‐Tsukui, 2006). Recent studies indicate in particular that trogo‐ and phagocytosis play a pivotal role in disease manifestations and host immune evasion (Miller, Suleiman, & Ralston, 2019; Nakada‐Tsukui & Nozaki, 2020; Ralston et al, 2014; Somlata, Nakada‐Tsukui, & Nozaki, 2017). It has been shown that both amebic trogo‐ and phagocytosis are energy dependent and require Gal/GalNAc lectin, protein and lipid kinases such as C2‐domain‐containing protein kinase (EhC2PK), atypical kinase (EhAK1), and phosphoinositide‐3‐kinase (PI3K), phosphatidylinositide‐binding proteins such as FYVE domain containing protein 4 (Nakada‐Tsukui, Okada, Mitra, & Nozaki, 2009) and SNXs (Watanabe, Nakada‐Tsukui, & Nozaki, 2020), and proteins involved in actin rearrangement such as calcium binding proteins, ArpA2/3, Rho/Rac, EhP3, and EhFP10 (Agarwal et al, 2019; Babuta et al, 2020; Babuta, Kumar, Gourinath, Bhattacharya, & Bhattacharya, 2018; Babuta, Mansuri, Bhattacharya, & Bhattacharya, 2015; Bharadwaj et al, 2018; Bharadwaj, Arya, Shahid Mansuri, Bhattacharya, & Bhattacharya, 2017; Gautam, Ali, Bhattacharya, & Gourinath, 2019; Nakada‐Tsukui et al, 2009; Powell et al, 2006; Ralston et al, 2014; Somlata, Bhattacharya, & Bhattacharya, 2011; Watanabe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…All of these processes require coordinated regulation of signal transduction, cytoskeletal reorganization, and vesicular trafficking (Aguilar‐Rojas, Olivo‐Marin, & Guillen, 2016; Babuta, Bhattacharya, & Bhattacharya, 2020; Nozaki & Nakada‐Tsukui, 2006). Recent studies indicate in particular that trogo‐ and phagocytosis play a pivotal role in disease manifestations and host immune evasion (Miller, Suleiman, & Ralston, 2019; Nakada‐Tsukui & Nozaki, 2020; Ralston et al, 2014; Somlata, Nakada‐Tsukui, & Nozaki, 2017). It has been shown that both amebic trogo‐ and phagocytosis are energy dependent and require Gal/GalNAc lectin, protein and lipid kinases such as C2‐domain‐containing protein kinase (EhC2PK), atypical kinase (EhAK1), and phosphoinositide‐3‐kinase (PI3K), phosphatidylinositide‐binding proteins such as FYVE domain containing protein 4 (Nakada‐Tsukui, Okada, Mitra, & Nozaki, 2009) and SNXs (Watanabe, Nakada‐Tsukui, & Nozaki, 2020), and proteins involved in actin rearrangement such as calcium binding proteins, ArpA2/3, Rho/Rac, EhP3, and EhFP10 (Agarwal et al, 2019; Babuta et al, 2020; Babuta, Kumar, Gourinath, Bhattacharya, & Bhattacharya, 2018; Babuta, Mansuri, Bhattacharya, & Bhattacharya, 2015; Bharadwaj et al, 2018; Bharadwaj, Arya, Shahid Mansuri, Bhattacharya, & Bhattacharya, 2017; Gautam, Ali, Bhattacharya, & Gourinath, 2019; Nakada‐Tsukui et al, 2009; Powell et al, 2006; Ralston et al, 2014; Somlata, Bhattacharya, & Bhattacharya, 2011; Watanabe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the adherence of Eh to host cells could mediate multiple cell cytotoxicity including promotion of cell death via phagocytosis, apoptosis, and trogocytosis those would play crucial roles in immune invasion [ 31 ]. Miller et al [ 4 ] further confirmed that amoebic trogocytosis by acquisition and displaying human cell membrane proteins could facilitate escape from immune lysis by human serum.…”
Section: Trogocytosis-associated Cytopathic Effects Immune Evasiomentioning
confidence: 99%
“…Partial phagocytosis, cell nibbling or cannibalization is also different names for trogocytosis [ 2 ]. This cellular growth behavior was first observed among amoebas [ 3 , 4 ] and then between cells of the immune system [ 5 ].…”
Section: Introductionmentioning
confidence: 95%
“…This plasmid, or a corresponding vector control, was transfected into amoebae using Attractene transfection reagent (Qiagen), and then stable transfectants were selected and maintained with Geneticin at 6 µg/mL (Invitrogen). Clonal lines were obtained by limiting dilution, and silencing was confirmed using RT-PCR (Miller, 2019). A single clonal line was used for experiments.…”
Section: Knockdown Mutantsmentioning
confidence: 99%
“…To enable quantitative cell death measurements, we previously developed an assay using imaging flow cytometry (Ralston, 2014). In this assay, amoebae and human cells are fluorescently labeled, allowing for trogocytosis to be directly measured, and Live/Dead Violet is used to stain dead (permeable) cells (Ralston, 2014, Gilmartin, 2017, Miller, 2019. This assay allows for automated analysis of thousands of images per sample, but is limited in practicality since imaging flow cytometers are not widely available.…”
Section: Introductionmentioning
confidence: 99%